Gender politics and security discourse personal-political imaginations and feminism in "post-conflict" Serbia - McLeod, Laura (War, politics and experience, 2016)
The volume explores in detail how feminist and women's organisations have responded to UNSCR 1325 by analysing two policy debates and campaigns that seek to 'achieve' its goals and gender security in Serbia: (1) feminist antimilitarism and (2) connecting domestic violence to the abuse of small arms and light weapons. Ultimately, the book argues that the configuration of gender security discourse is intimately linked to personal-political imaginations of conflict and post-conflict. This book will be of much interest to students of gender politics, conflict studies, critical security studies, European politics and IR in general.